MASTER Learning Model: Motivating, Acquiring, Searching, Triggering, Exhibiting, and Reflecting toward Students' Mathematical Reasoning - Nazilah, Rohmah Li'izzatun; Amir, Mohammad Faizal (Jurnal Pendidikan Progresif, 2025)
MASTER Learning Model: Motivating, Acquiring, Searching, Triggering,  Exhibiting, Reflecting toward Students Mathematical Reasoning. Objectives: This study aims to analyze the effect of the MASTER learning model (motivating, acquiring, searching, triggering, exhibiting, and reflecting) on students' mathematical reasoning. Methods: This study is classified as a quasi-experiment involving participants engaging fifth-grade students in two Sidoarjo primary schools. The study design was a pre-test, post-test-only control group involving the experiment and control classes. The experiment class implemented the MASTER learning model, and the control class implemented conventional learning. Learning in both classes used the same material, namely building space.  The sample was selected using a purposive sampling technique, with one class in one primary school in Sidoarjo as the experimental class and one primary school in Sidoarjo as the control class. The study instrument used a mathematical reasoning test to measure three components of mathematical reasoning: analysis, generalization, and justification. Validity and reliability tests were conducted before the mathematical reasoning test was used. Data analysis used descriptive and inferential. Descriptive analysis includes the calculation of mean, standard deviation, and effect size. Meanwhile, inferential analysis uses an independent t-test with two prerequisite tests: normality and homogeneity. Findings: This study's result shows a significant impact of the MASTER learning model on students' mathematical reasoning. In this case, the effect size is confirmed in the large category of mathematical reasoning. Descriptive study results show that there is a difference between students who follow MASTER learning and students who follow conventional learning. The difference can be seen in the value of students' mathematical reasoning component. In this case, the highest to smallest differences in mathematical reasoning components are analysis, justification, and generalization. Conclusion: The MASTER learning model can significantly impact enhancing students' mathematical reasoning in elementary school. Consecutively, enhancing mathematical reasoning is confirmed in the components of analysis, justification, and generalization. Keywords: MASTER learning model, mathematical reasoning, primary students.